"The prayer circles in the air": a qualitative study about traditional healer profiles and practice in Northern Norway - Larsen, Anette Langås; Salamonsen, Anita; Kristoffersen, Agnete Egilsdatter; Stub, Trine (International Journal of Circumpolar Health, 2018)
Source at https://doi.org/10.1080/22423982.2018.1476638. © 2018 The Arctic University of Norway, Tromsø In Northern Norway, traditional healing has been preserved by passing down the knowledge through generations. Religious prayers of healing ( reading ) and Sami rituals ( curing ) are examples of methods that are used. We have examined traditional healers’ understanding of traditional healing, the healing process and their own practice, as well as what characteristics healers should have. Semi-structured individual interviews and focus group interviews were conducted among 15 traditional healers in two coastal Sami municipalities in Norway. The traditional healers understood traditional healing as the initiation of the patient’s self-healing power. This power was initiated through healing rituals and explained as the power of God and placebo effect. During the healing ritual, the doctor’s medical diagnoses, the patient’s personal data and a prayer in the name of The Father, The Son and The Holy Spirit were used in combination with steel and elements from the nature. The traditional healers stated that they had to be trustworthy, calm and mentally strong. Healers who claimed that they had supernatural abilities (clairvoyant or warm hands) were regarded as extra powerful. According to the participants in this study, the healers must be trustworthy, calm and mentally strong. Moreover, these traditional healers drew on information from conventional medicine when performing their rituals.